Representasi Feminisme Dalam Manhwa Ebony Di Kakaopage (Analisis Wacana Kritis Sara Mills) - Dewi, Dewa Ayu Prisma Yana; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium; Vol 4 No 1 (2023): Jurnal Ilmu Komunikasi Vol 4 No 1 Tahun 2023, 2023)
Women in the mass media, basically talk about the women representation in the mass media, the media has always made women as an object. The depiction of women in the mass media is often stereotyped. One of the mass media that still stereotypes women is comics. Women are often portrayed as victims in the comics. There is a korean comics depicting a woman who is different from the general stereotype. In South Korea, comics published online and in print are called Manhwa. The Manhwa called Ebony, features a woman who has an ambitious, confident, courageous and feminist figure who breaks her country's patriarchal system for gender equality. This study aims to clarify how the representations of feminism on Ebony Manhwa in Kakaopage. This research used a descriptive qualitative research method using criticaI discourse anaIysis by Sara Mills. The resuIts of this study showed that there are two types of feminism represented in this Manhwa. There is Iiberal feminism, as shown by the resistance movement to achieve gender equality and women's rights, and post-modern feminism, as shown by women who are intellectual, strong, confident, brave and woman support woman. Keyword: Representation, Feminism, Manhwa, Kakaopage, Sara Mills Critical Discourse Analysis